STRATEGI PEMASARAN DIGITAL MELALUI PLATFORM MEDIA SOSIAL PADA UMKM CUPU MANIK KERAMIK DI PURWAKARTA - Reza Saleh; Meliana Nurjanah; Ai Rohmah; Aidah Nur Fadhilah; Wahyu Yulianto (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Cupu Manik Keramik is a producer of earthenware and decorative ceramics located in Plered District, Purwakarta, which faces limited market reach due to the absence of digital marketing and reliance on conventional promotion. This community service program aims to enhance business visibility through the implementation of promotional strategies using short-form social media platforms. The approach involved observation, interviews, content creation, and publication assistance conducted from August to September 2025. A total of eleven contents were published, including product catalogs, production processes, stock documentation, promotional materials, and store information. The highest-performing contents were the product catalog and stock documentation, while the lowest were product documentation and store information. These findings indicate that informative and visually varied content is more effective in attracting audience attention and providing initial exposure. Therefore, digital marketing through short-form social media has the potential to become an effective strategy for expanding the market reach of craft-based MSMEs.